Interactive Augmented Reality Web for Introduction to Plants in the Sukolelo Prigen Herbal Village - Achmad Alfi Fakhresi; Rohman Dijaya (Universitas Muhammadiyah Sidoarjo, 2022)
The use of existing technology in Indonesia is still not widely applied. Even the information on the internet about the tourist attractions of the Kampung Herbal Sukolelo Prigen is still incomplete. Therefore, we need a solution to facilitate the introduction of existing herbal plants, so that tourists are more interested in coming to this tourist spot. Augmented Reality (AR) applications have the ability to display multimedia content from PCs, laptops, smartphones, and other devices. Augmented Reality (AR) is widely used in the fields of entertainment, games, advertising, education, health, commerce, as well as industry. This application will display 3D objects of herbal plants by scanning the camera from the user's device against a predetermined marker. Later the marker will be printed and placed in a special place. Then each marker will display a 3D object of herbal plants and the other supporting attributes. This application is expected to make it easier for tourists to recognize existing herbal plants. This application in the future is able to display 3D objects in the form of herbal plants and other attributes as supporting information.